2015
DOI: 10.17219/acem/43761
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Epigallocatechin Gallate Against Distant Organ Damage After Severe Skin Burns – Experimental Study Using a Rat Model of Thermal Trauma

Abstract: Background. Epigallocatechin gallate (EGCG), a green tea polyphenol, has potent antioxidant properties. Objectives. The purpose of the present study was to examine the possible preventative effects of EGCG against internal organ injury due to large-surface skin burns in a rat model. Material and Methods. The study design involved three groups of rats: a sham group and two groups with 25-30% full-thickness burns: (a) the sham group without burns or treatment (n = 18); (b) the control burn group (burns + sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…These results are in line with the findings reported by Ali Akbar Abolfathi et al (2012) who observed that daily treatment with green tea extract markedly improved antioxidant status of liver tissue of rats with streptozotocin induced diabetes. Moreover in a burn model Hosnuter et al (2015), epigallocatechingallate (EGCG), exerted a potent antioxidant effect. In the EGCG-treated burn group, superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities were significantly higher than in the burn wounded control group.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with the findings reported by Ali Akbar Abolfathi et al (2012) who observed that daily treatment with green tea extract markedly improved antioxidant status of liver tissue of rats with streptozotocin induced diabetes. Moreover in a burn model Hosnuter et al (2015), epigallocatechingallate (EGCG), exerted a potent antioxidant effect. In the EGCG-treated burn group, superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities were significantly higher than in the burn wounded control group.…”
Section: Discussionmentioning
confidence: 99%
“…Post-recovery burn areas were evaluated by immunohistochemical staining. The aim here is to investigate the efficacy of the PcTx 1 venom, which we think accelerates the healing of various grades of burn injury after thermal injury [21] .…”
Section: Histopathological Assessmentmentioning
confidence: 99%
“…Tannins can precipitate proteins on cell surfaces and polyphenols, which have many health benefits because they have antioxidant activity with strength 100 times more effective than vitamin C and 25 times higher than vitamin E (Prastiwati et al, 2010). Additionally, EGCG is a polyphenol in green tea that possesses antiinflammatory, anti-microbial, and anti-allergic properties (Hosnuter et al, 2015).…”
mentioning
confidence: 99%